Pengaruh Motivasi, Biayapendidikan, Dan Lama Pendidikan Terhadap Minat Mahasiswa Akuntansi Mengikuti Pendidikan Profesi Akuntansi : Studi Empiris Pada Mahasiswa Akuntansi Universitas Nusa Nipa - Maria Enyelistike Sado; Andreas Rengga; Siktania Maria Dilliana (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of motivation, cost of education and length of education on the interest of accounting students to take Accounting Professional Education (PPAk). This research method is a quantitative method. Data analysis used multiple regression analysis which was calculated using the IMB SPSS 26 program. The hypothesis test used was a simultaneous test (F test), partial test (t test), and test of the coefficient of determination (R2 test). The population in this study were 132 active semester VIII students of the accounting study program at Nusa Nipa Maumere University. The results of this study indicate, based on the results of the F test simultaneously the variables of motivation, tuition fees and length of education have a significant effect on the interest of accounting students to take PPAk. However, based on the t test, only motivation has an influence and is significant on the interest of accounting students to take PPAk with a tcount > ttable (6.342 > 2.000) and a significant value of 0.000 <0.05. while the cost of education and length of education did not affect the interest of accounting students to take PPAk with tcount < ttable (0.881 < 2.000) and tcount < ttable (1.169 < 2.000).